Pengenalan dan Pelatihan Teknologi Internet Of Things Dan Robotika Bagi Siswa Sekolah Menengah Kejuruan - Aris Sudianto; Muhammad Wasil; Baiq Andriska Candra Permana; Muhamad Sadali (Jurnal Teknologi Informasi untuk Masyarakat, 2026)
This Community Service (PKM) activity is entitled "Introduction and Training of Internet of Things (IoT) and Robotics Technology for NWDI Wanasaba Vocational High School Students" which is implemented using the Participatory Learning and Action (PLA) method. This activity is motivated by the need to improve student competency in facing the Industrial Revolution 4.0 era, where mastery of IoT and robotics is an important skill for both the industrial world and technology-based entrepreneurship. The PLA method was chosen because it emphasizes the active involvement of participants in the entire learning process through discussions, direct practice, and joint reflection. The stages of the activity include identifying partner needs, designing training materials, implementing practice-based training, to evaluating the results of the activity. Students are involved participatory in every stage, starting from the introduction of basic concepts of IoT and robotics, practicing assembling devices, simple programming, to testing applications in the context of everyday life and vocational fields. The results of the activity show that students gain increased knowledge, technical skills, and motivation to innovate in utilizing technology. Through this activity, three main outcomes were achieved: (1) increasing digital and technological literacy for students, (2) forming basic competencies in IoT and robotics that can be further developed, and (3) establishing  collaboration between universities and schools in supporting the strengthening of vocational education. Thus, this PKM not only contributes to improving the quality of human resources in the NWDI Wanasaba Vocational School environment, but also becomes a strategic step in preparing the younger generation to face the challenges of the digital era.